Prevalence of substance use among college students of State Colleges in Iloilo City - Agreda, Joji Marie Gela
This study aimed to describe the prevalence, nature, and extent of substance use of college students enrolled in the main campuses of state colleges in Iloilo., There were 402 respondents coming from the man campuses of Iloilo State College of Fisheries (SCOF), Northern Iloilo Polytechnic State College (NIPSC), Western Visayas College of Science and Technology (WVSCT) and the lone campus of New Lucena Polytechnic College (NLPC). Data was collected through a questionnaire which was modified from the model core questionnaire developed by the World Health Organization (WHO). Results showed that 36.1% of the respondents had tried smoking. Their mean age of smoking initiation was 17 years with 13.5% having first tried smoking before 15 years of age. Their top reasons for smoking are as follows: curiosity (44.1%), for fun (25.5%) and peer pressure (17.2%). Of the respondents who smoked within 30 days prior survey, 14.7% consumed more than 5 cigarettes per day. the result also showed that 33.8% of the respondents who have tried smoking usually smoke during parties while their usual place to smoke is either in their houses, dormitories or boarding houses (40.7%). There was a significant relationship between the smoking status of the respondents who have tried smoking and the following: gender (p<0.0001), age (p=0.0004) and year level (p<0.01). On the other hand, smoking status of the respondents who have tried smoking has no significant relationship with the following: annual family income (p=0.91), living arrangement (p=0.63) and membership in fraternities/sororities (p=0.17). Alcoholic use had a higher prevalence (65.4%) than cigarette smoking (36.1%). The mean age of the respondents who have tried drinking was also 17 years with (31.1%). The mean age of those respondents who have tried drinking was also 17 years with 13.7% having tried drinking at an age below 15 years. Their top three reasons for drinking are: for fun (34.6%), curiosity (29.3%) and because family drink (12.9%). Seventy percent of the respondents who have tried drinking drank 30 days prior to the survey with 10.9% consuming more than 5 bottles and another 10.9% consuming more than 5 glasses of alcoholic beverages. Of those who have been binge drinking 30 days prior to the survey, 18.9% have been binge drinking 3 to 5 times. The usual occasion for the respondents to drink is during parties (72.9%) and the usual place for them to drink was either in their houses, dormitories or boarding houses (60.8%). The beverage of choice is beer (59.7%). The drinking status of those who have tried drinking had a significant relationship with the following: gender (p < 0.0001), a year level (p=0.005) and membership to fraternities/sororities (p = 0.04). Meanwhile drinking status had no significant relationship to with age (p = 0.06), annual family income (p = 0.85) and their living arrangements (p = 0.51). Shabu use had a prevalence of 2.7% among the respondents. The mean age of shabu use was also 17 years with 18.2% first first trying it at 15 years of age. Their reasons for having tried shabu are: peer pressure (45.5%), curiosity (18.2%) and for fu (18.2%). Within 30 days prior to the survey, 45.5% of those who has tried using shabu have used shabu and 20.0% have used shabu in 20 or more days. They usually use shabu during parties (54.5%) and usually have tried using shabu either in their houses, dormitories and boarding houses (54.6%). Data shows that shabu use had a significant relationship with the following: gender (p = 0.0007), a year level (p = 0.003) and fraternity/sorority membership (p = 0.05). It has no significant relationship with age (p = 0.09), annual family income (p = 0.92) and their living arrangements (p = 0.47). Results also showed that 5% of the respondents have tried smoking marijuana and 4.2% have tried opiate type drugs. The mean age for having tried drugs other than shabu was also 17 years with 26.3% having tried them at an age below 15. Thirty-one percent of those who have tried other drugs than shabu have tried within 30 days prior to the survey.